2019
DOI: 10.1103/physrevresearch.1.033057
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuniform vortex patterns at the surface of type-II superconductors

Abstract: A many-particle system must posses long-range interactions in order to be hyperuniform at thermal equilibrium. Hydrodynamic arguments and numerical simulations show, nevertheless, that a three-dimensional elastic-line array with short-ranged repulsive interactions, such as vortex matter in a type-II superconductor, forms at equilibrium a class-II hyperuniform two-dimensional point pattern for any constant-z cross section. In this case, density fluctuations vanish isotropically as ∼ q α at small wave-vectors q,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…periodic distributions of pinning sites 17 . Recently, some studies focusing on characterizing long 46,60 or shortrange 47 vortex density fluctuations obtained contrasting results for samples with point or correlated disorder, see the discussion in Supplementary Note 1. From the perspective of technological applications, having information on the nature and distribution of disorder in a given sample is crucial since correlated in addition to point-like disorder is more efficient to pin vortices and thus to enhance the material critical current 12 .…”
mentioning
confidence: 99%
“…periodic distributions of pinning sites 17 . Recently, some studies focusing on characterizing long 46,60 or shortrange 47 vortex density fluctuations obtained contrasting results for samples with point or correlated disorder, see the discussion in Supplementary Note 1. From the perspective of technological applications, having information on the nature and distribution of disorder in a given sample is crucial since correlated in addition to point-like disorder is more efficient to pin vortices and thus to enhance the material critical current 12 .…”
mentioning
confidence: 99%
“…As a result, it may be possible to determine whether elastic, fragile, jammed or pinned behavior is likely to occur by examining the vortex configurations even before a drive is applied. This can be achieved experimentally using a variety of imaging techniques [56][57][58][59] .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, vortex lattices at very small magnetic fields were analyzed in view of their hyperuniform properties. Those authors analyzed images of the high-T c cuprate superconductor Bi 2 Sr 2 CaCu 2 O 8+δ with magnetic Bitter decoration in the presence of disorder [23]. At small magnetic fields, vortices are very far apart and their mutual repulsion is small [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of Ref. [23] concluded that long-wavelength fluctuations are systematically suppressed in the vortex lattice at small magnetic fields, as a consequence of the hydrodynamic properties of the liquid phase, which leads to deviations from fully random vortex distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation